SEROLOGICAL ANTIBODY RESPONSE OF THE CLASSES IgM AND IgG ANTI-Toxoplasma gondii IN DOGS WITH OCULAR ALTERATIONS. - Rodrigues, Nássarah Jabur Lot; Manzini, Suzane; Oliveira, Natalie Newirt; Gava, Mariana Zanchetta e; Gonçalves, Lenise Garbelotti; Hirota, Inajara Nakaruma; Ferreira, Annalu Pinton; Sessa, Mariana De; Ferreira, Mayara Chagas; Reiter, Luis Felipe Fernandes; Brandão, Claudia Valeria Seullner; Langoni, Helio; et al. (Archives of Veterinary Science, 2021)
Toxoplasmosis is a worldwide zoonosis capable of infecting a wide variety of animal species and humans. It is caused by the protozoan Toxoplasma gondii, which causes a silent disease with ophthalmic alterations such as uveitis in dogs, in addition to neuromuscular symptoms and pneumonia. The present study aimed to detect IgM and IgG class antibodies against T. gondii in 75 dogs with ophthalmic signs, treated at the Veterinary Hospital of FMVZ Unesp, Botucatu campus. Serological results for the detection of IgM and IgG class antibodies were evaluated by the Indirect Immunofluorescence Reaction (RIFI) technique associated with data from a questionnaire regarding the risk factors for toxoplasmosis in the canine species administered to the animal's guardian on the day of blood collection. The results were statistically evaluated according to the researched variables, ocular alterations and serological results. Results were 28/75 (37%) for IgG class antibodies and 34/75 (45%) for IgM class.